PRACTICAL AND COMPETENTIAL APPROACHES AS A METHODOLOGICAL BASIS FOR THE PROFESSIONAL TRAINING OF FUTURE MUSIC TEACHERS - Мітєва, Арина; Врубель, Ганна (SWorldJournal, 2023)
The article highlights the practical and competence approaches as a methodological basis for the professional training of future music teachers. The author reveals the practical approach from the point of view of practice-oriented activity of a music teac